Analisis Kelayakan Video Pembelajaran Matematika SMP Kurikulum 2013 Materi Bangun Ruang Sisi Datar Pada Platform Youtube - Mahdiah, Athiatul; Kristayulita, Kristayulita; Nasrullah, Ahmad (Mathematic Education Departement, State Islamic University of Mataram, 2023)
Abstract This research was conducted to determine the level of feasibility of the 2013 Curriculum Junior High School mathematics learning video on flat-sided space on the YouTube platform. The limitation in this study is the study of the feasibility of learning videos from the content aspect, presentation aspect, language aspect, and graphic aspect. The subjects in this study were videos of junior high school mathematics learning curriculum 2013 material on the flat side of 8 youtube channels which were selected using a sampling technique, namely the purposive sampling technique. This purposive sampling technique is used to select videos based on the time they were uploaded. The videos were then validated by 3 math teachers. The instruments used in this study were the feasibility study sheet for the learning video and the reasoning sheet for the video feasibility assessment by the respondents. The data analysis used is data reduction, data presentation, and conclusion drawing. The results of this study are the overall level of video feasibility, namely learning videos from 3 youtube channels are categorized as